2022
DOI: 10.1177/09636897221119734
|View full text |Cite
|
Sign up to set email alerts
|

Unique Challenges to Diagnosing Human Herpesvirus-6 (HHV-6) Encephalitis Following Post-Hematopoietic Stem Cell Transplant: A Case and Brief Review

Abstract: A patient with an ultimate diagnosis of human herpesvirus-6 (HHV-6) encephalitis developed central nervous system (CNS) symptoms 13 days after undergoing myeloablative haploidentical allogeneic hematopoietic stem cell transplant (HSCT). Due to the patient’s body habitus, magnetic resonance (MR) imaging was not obtained until the onset of retrograde amnesia on day +24. MR imaging and other clinical findings eliminated all skepticism of HHV-6 encephalitis and HHV-6 antivirals were initiated on day +28, leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…While HHV-6 is a known cause of encephalitis after HSCT, its role in enteritis has rarely been reported. Only few smallscale retrospective studies reported the incidence of HHV6 intestinal infection after transplantation (23)(24)(25). Previous studies by Perruccio et al(26) reported that HHV6-related enteritis was observed only in 3.3% of the 123 pediatric patients post HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…While HHV-6 is a known cause of encephalitis after HSCT, its role in enteritis has rarely been reported. Only few smallscale retrospective studies reported the incidence of HHV6 intestinal infection after transplantation (23)(24)(25). Previous studies by Perruccio et al(26) reported that HHV6-related enteritis was observed only in 3.3% of the 123 pediatric patients post HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…HHV-6 reactivation outside of DRESS has been associated with severe and significant complications, including multiorgan system involvement and autoimmune sequelae. 5,[84][85][86][87][88] However, testing for HHV-6 infection can be nuanced. As >90% of individuals are seropositive for latent IgG HHV-6 antibodies, serology taken at 1 point in time is not an ideal determinant of active infection.…”
Section: Discussionmentioning
confidence: 99%
“…In HSCT patients, ganciclovir and foscarnet have demonstrated efficacy and are currently recommended for treatment of severe HHV-6 sequelae (i.e., HHV-6 encephalitis). 88 While clinical efficacy is unconfirmed, cidofovir and its derivatives have also shown in vitro activity against HHV-6. 106 IVIG treatment is pooled antibody replacement therapy primarily indicated for immunodeficient states, as in bone marrow transplantation or HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Is reduction of active HHV-6 replication or administration of ganciclovir associated with decreased post-DRESS sequelae, including autoimmune diseases or DRESS recurrence? Given the body of evidence for the efficacy of antiviral treatment in HHV-6 encephalitis, an HHV-6-driven disease with high mortality and morbidity, 12 we propose that similar benefit may be observed with antiviral treatment in DRESS.…”
mentioning
confidence: 95%